On our own strength : the self-reliant literary group and cosmopolitan nationalism in late colonial Vietnam - Nguyen, Martina Thucnhi (Studies of the Weatherhead East Asian Institute, Columbia University., 2021)
"On Our Own Strength examines the political activities of the most influential intellectual movement in interwar French-occupied Vietnam. The far-reaching work of the Self-Reliant Literary Group (Tự Lực Văn Đoàn) included applied design, urban reform, fashion, literature, journalism, and cartoons; its work was deeply political in both form and intent. The Group drew upon a wide range of global intellectual currents and practices to build an enlightened public that would one day serve as the basis of a modern Vietnamese nation. Its nationalist vision sought a nonviolent middle path between colonialism and anticolonial struggle, advocating a process of gradual decolonization that ultimately ended in Vietnamese autonomy. This form of cosmopolitan nationalism proved tremendously popular among ordinary Vietnamese and necessarily shaped local politics, influencing the political agenda of even rival groups such as the newly revived Indochinese Communist Party (ICP). On Our Own Strength shows how the Group's vision shaped the ways ICP positioned itself and sought popular support in the years leading up to the August Revolution and beyond. In later years, the party attempted to erase the Group's early influence on national politics, banning their writings and casting them as little more than bourgeois literary figures. In recovering the Group's unique response to the world around them, this book bridges the areas of political, cultural, and intellectual history, drawing them together into a rich narrative of Vietnamese nation-building from the bottom-up within a larger global context. Martina Thucnhi Nguyen offers a powerful model for the field of Vietnamese studies as it continues to move beyond simplistic and political narratives of its most tumultuous period. Groundbreaking in perception, her book engages broadly with global history, European history, and imperial studies to explore colonialism's hybrid cultural and political forms. She examines how the Self-Reliant Literary Group weighed in on everything from women's fashion and public housing to the major political ideologies of the era, in a unique style that mixed French-inflected ideas with Vietnamese norms and forms. As a deep case study of important figures on the Vietnamese moderate left, On Our Own Strength provides an injection of color and nuance into a history that is often too monochromatic"--